Prospects of Wellness Tourism in Indonesia as Tourism Sector Recovery Effort Post Covid-19 Pandemic - Francisca Titing Koerniawaty; I Made Sudjana (Budapest International Research and Critics University, 2022)
Tourism in Indonesia has suffered a devastating blow during the COVID-19 pandemic, therefore various efforts need to be taken to restore tourism. The type of tourism that is becoming a trend today is tourism that accommodates the issue of improving the quality of healthy life to achieve a balance of body, mind, and spirit (wellness tourism). Indonesia as a country that is rich in natural resources and has a variety of traditional cultures in each region, should have good prospects for the development of wellness tourism. This study aims to explore tourist attractions in areas in Indonesia that have the potential to be developed as wellness tourism. This type of research is descriptive qualitative with data collection methods through literature study. The research instruments used are aspects of the body (physical wellness), mind (intellectual wellness, emotional wellness, social wellness), and soul (spiritual wellness). Research findings indicate that tourism objects in Indonesia contain wellness tourism aspects, namely: 1) Body aspects in the form of nature tourism (island tourism, hot spring tourism, and marine tourism) with attractiveness in the form of tourism activities related to tourism physical health; 2) Mind aspects in the form of educational tours (traditional medicine tours, unique village tours, and certain plant cultivation tours); 3) The soul aspect is in the form of religious and historical tourism (tours to historical places of worship, historical sites, and tombs of prominent figures, such as scholars and kings). From these findings, it can be concluded that tourism objects in Indonesia have the potential to be developed into wellness tourism. This research is important as a recommendation material for the government and stakeholders to develop a tourism recovery model by prioritizing tourism objects with the concept of wellness tourism.